Adverse local tissue reaction after 2 revision hip replacements for ceramic liner fracture: A case report. Issue 19 (May 2017) - Antoniac, Iulian; Negrusoiu, Mihai; Mardare, Mihai; Socoliuc, Claudiu; Zazgyva, Ancuţa; Niculescu, Marius
Abstract: Introduction: In younger patients, ceramic-on-ceramic (CoC) bearing surfaces are usually recommended for total hip replacement (THR) because of their low wear rate and longer expected functional life. Although technical advancements have reduced the risk of ceramic bearings fracture, this complication remains a major concern. Case description: We present the case of a 56-year-old patient undergoing 3 revision hip arthroplasties of the right hip due to ceramic liner fractures. Initial THR (2008) was performed with a CoC bearing, followed by liner fracture due to trauma a year later. The acetabular component and liner were replaced, with a minor incongruence between the old head and new insert. The 2nd ceramic insert fractured 3.5 years later, following minor trauma. Upon revision, the bearing surface was changed to metal-on-polyethylene (MoP). The performed retrieval analysis demonstrated stripe and rim wear, and evidence of adhesive wear. The patient was referred to us a month later, with a fistula on the lateral side of the hip, discharging black, petroleum-like liquid. Radiology showed well-fixed implants, no dislocation and no apparent polyethylene wear. Microbiological assessment of the discharge showed no infection. Intraoperatively massive metallosis was noticed, with stable acetabular and femoral components. The metal femoral head was heavily abraded, with almost 1% volumetric wear. Hematoxylin and eosin stained frozen tissue samples showed muscular and adipose tissue necrosis, while polarized light microscopy highlighted metal, polyethylene, and ceramic particles. Conclusion: The present case is yet another report showing the adverse outcomes of using MoP bearings for revision after ceramic liner fracture in THR.